Influence of COVID-19 for delaying the diagnosis and treatment of pulmonary tuberculosis–Tianjin, China - Zhang, Guoqin; Yu, Yanming; Zhang, Wenqian; Shang, Jian; Chen, Shengyu; Pang, Xuewen; Oeltmann, John E.; Moonan, Patrick K.; Chen, Mingting; Zhang, Fan (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has disrupted the diagnosis, treatment, and care for tuberculosis (TB). Delays in seeking TB care may result in increased community transmission and unfavorable treatment outcomes. We sought to understand the influence of the COVID-19 pandemic on the proportion of patients with TB who delayed seeking the diagnosis and care for TB and explore the reasons for their postponement. Methods We surveyed a representative sample of outpatients treated for pulmonary TB from June to November 2020 using an anonymous standardized questionnaire. Multivariable logistic regression was used to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CIs) of factors associated with the postponement of TB care. We used routinely collected surveillance data to assess trends of TB reports before and after the emergence of COVID-19 (2017–2019 vs. 2020–2022) in Tianjin, China. Results Among 358 participants who were diagnosed with pulmonary TB during the COVID-19 response, 61 (17%) postponed seeking TB diagnosis due to COVID-19, with 39 (64%) citing fear as the primary reason. Female sex (aOR:2.0; 95% CI: 1.1–3.7), previous antituberculosis treatment (aOR:3.2; 95%CI: 1.4–7.6), and TB diagnosis during the first-level response (aOR = 3.2, 1.7–6.2) were associated with the postponement. Among all 518 participants receiving antituberculosis treatment, 57 (11%) had postponed their regular healthcare visits due to COVID-19, 175 (34%) received no treatment supervision, and 32 (6%) experienced treatment interruption. Compared to 2017–2019, reported pulmonary TB declined by 36.8% during the first-level response to COVID-19, 23.5% during the second-level response, 14% during the third-level response in 2020, and 4.3% in 2021. Conclusion The COVID-19 response reduced the number of people who sought and received diagnosis, treatment, and care for TB in Tianjin, China. Integrative programs to ensure access and continuity of TB services should be considered and dual testing for SARS-CoV-2 and M. tuberculosis may facilitate finding cases.